Pengaruh Aplikasi Edible Coating Gel Lidah Buaya dan Kitosan terhadap Mutu Buah Stroberi pada Penyimpanan Suhu Ruang dan Suhu Rendah - Astutiningsih, Astutiningsih; Noertjahyani, Noertjahyani; Mulya, Hudaya; Aisyah, Iis (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
Strawberries are nonclimateric fruits harvested in the final stages of ripening, so they are highly damaged due to cellular fragility, high respiration rate, and susceptibility to fungal growth. This study aims to test the effectiveness of edible coating of aloe vera gel and chitosan to maintain the quality and shelf life of strawberries. The study was carried out by experimental method with split plot by group random design. Storage temperature treatment as the main plot consists of two treatment levels, namely 25±2o C and 4±1o C, while the concentration of edible coating combination as a plot consists of five treatment levels, namely control without edible coating, aloe vera gel 40%, chitosan 2%, aloe vera gel 40% + chitosan 2%, and aloe vera gel 20% + chitosan 1%. Quality attributes including weight loss, fruit hardness, total dissolved solids, decay index, and shelf life are observed until total deterioration occurs. The results showed that at a storage temperature of 25±2° C, chitosan 2% treatment was more able to maintain the quality attributes of strawberries compared to other treatments. Meanwhile, at a storage temperature of 4±1°C, edible coating treatment of 40% aloe vera gel and 40% aloe vera gel + 2% chitosan which more effectively maintains the quality attributes of strawberries. However, for shelf life parameters, only the temperature factor of the storage room affects the length of shelf life of strawberries. The longest shelf life is achieved at low temperature storage (4±1°C) with edible coating treatment of 40% aloe vera gel + 2% chitosan (13.33 days). However, according to the LSD test at a real level of 5%, this value was not significantly different from other edible coating treatments stored at low temperatures, including the lowest shelf life that occurred in controls without edible coatings (10.67 days).